Bottling plant location of microbreweries in East Midlands area, UK - Zheng, Chi (2013)
Facility location decisions are critical in real-life projects, which impact on profitability of investment and service levels from demand side. In this paper, a project-based facility location problem should be resolved which refers to the establishment of a centralized bottling plant to serve microbreweries in East Midlands area of UK. This problem will be structured by firstly finding a mathematically theoretical location using the centre-of-gravity method and then formulate the problem as a multi-criteria decision making problem applying Analytical Hierarchy Process based on selection of the optimal location out of the four candidate locations where three of those have been given. The second part is modeled by considering several criteria related to both the activities before and after bottling and also issues of surrounding area of the location where the prioritization of those criteria are based on the preferences of the project investor. The final result is obtained by applying EXPERT CHOICE to approach Eigenvalue methods to enhance Analytical Hierarchy Process. The outcome can be clarified with illustration of the sensitivities resulted from the weight changes of criteria and the pull-out of certain criteria.